Etiological factors of voiding disorders in females - Inga V. Kosova; Vagan A. Barsegian; Oleg B. Loran; Liubov A. Sinyakova; Igor' V. Luk'ianov; Dmitrii N. Kolbasov; Aleksandr N. Kruzhalov; Malakhat I. Alieva (ZAO "Consilium Medicum", 2022)
Background. Voiding disorders in females are a serious medical and social problem. Various urological, gynecological, and neurological factors contribute to the development of these disorders. Aim. To study etiological factors of voiding disorders in females. Materials and methods. A total of 52 women 19 to 81 years of age with various voiding disorders were inspected. Examination algorithm included collection of a comprehensive medical history, filling in voiding diaries, gynecological exam, various laboratory tests (including PCR-diagnostics of urethral scrapings; ELISA tests for IgM and IgG to herpes simplex virus types 1 and 2, Varicella Zoster virus, EpsteinBarr virus, cytomegalovirus; vaginal discharge culture for flora and sensitivity to antibiotics, with mandatory determination of the lactobacilli count) and diagnostic methods, as well as consultations by related specialists. Results. Chronic herpesvirus infection contributed to urinary dysfunction in 28 (53.8%) women, bacterial urinary tract infection in 15 (28.8%), bacterial vaginosis in 15 (28.8%), papillomavirus infection in 12 (23.1%), and interstitial cystitis in 10 (19.2%) patients. Thirty-five (76.9%) women had several simultaneous factors that contributed to the development of voiding disorders. Conclusion. The combination of disorders of the vaginal microflora with viral and/or bacterial infections most often contributes to the development of voiding disorders.